Analysis Of The Role Of Parents In Early Childhood Islamic Religious Education In The Family Environment - Harahap, Aziddin (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The role and responsibilities of parents for preschool age children in an Islamic perspective are very important and very important in the development and formation of children's character and education because at this time it is very vital (golden age) for children's growth and development. , both in terms of physical growth, brain growth, and spiritual growth because at this time children will usually imitate what their parents do, whether their actions are good or bad. Therefore, parents must pay more attention to their children and educate them on good and positive things so that they become children who are beneficial to society, devoted to their homeland and nation. The research method in this journal was carried out by studying literature by analyzing theoretical data about the role of parents in children's Islamic education from an early age using various sources to form a comprehensive idea about how important the role of parents is in the formation of children. children's Islamic education is implemented. Since early stage. Every parent wants to educate their child well and successfully. They hope that their children will have the personality, faith and devotion to Allah AZZA WA JA'ALA. Children with noble character are filial to their parents and are beneficial to themselves, their family, society, homeland, state and religion. Efforts to educate children must start as early as possible so that children grow and develop into intelligent children. One of the earliest and most basic efforts is to pray to Allah AZZA WA JA'ALA, asking that the child who will be entrusted to us in the future will be a wise and devout child, and asking for guidance so that we will be given the ability to care for, care for and educate him in a way the good one. Islamic teachings. So, with the role and responsibility of parents in their children's Islamic religious education, children will become a successful generation in the afterlife and be able to serve their parents, homeland and nation.